SI-traceable validation of a laser spectrometer for balloon-borne measurements of water vapor in the upper atmosphere - S. Brunamonti; M. Graf; T. Bühlmann; C. Pascale; I. Ilak; L. Emmenegger; B. Tuzson (Atmospheric Measurement Techniques, 2023)
Despite its crucial role in the Earth's radiative balance, upper-air water vapor (H2O) is still lacking accurate, in situ, and continuous monitoring. Especially in the upper troposphere–lower stratosphere (UTLS), these measurements are notoriously difficult, and significant discrepancies have been reported in the past between different measuring techniques. Here, we present a laboratory assessment of a recently developed mid-IR quantum-cascade laser absorption spectrometer, called ALBATROSS, for balloon-borne measurements of H2O in the UTLS. The validation was performed using SI-traceable reference gas mixtures generated based on the permeation method and dynamic dilution. The accuracy and precision of ALBATROSS were evaluated at a wide range of pressures (30–250 mbar) and H2O amount fractions (2.5–35 ppm), representative of the atmospheric variability in H2O in the UTLS. The best agreement was achieved by implementing a quadratic speed-dependent Voigt profile (qSDVP) line shape model in the spectroscopic retrieval algorithm. The molecular parameters required by this parameterization were determined empirically using a multi-spectrum fitting approach over different pressure conditions. In the laboratory environment, ALBATROSS achieves an accuracy better than ±1.5 % with respect to the SI-traceable reference at all investigated pressures and H2O amount fractions. The measurement precision was found to be better than 30 ppb (i.e., 0.1 % at 35 ppm H2O) at 1 s resolution for all conditions. This performance, unprecedented for a balloon-borne hygrometer, demonstrates the exceptional potential of mid-IR laser absorption spectroscopy as a new reference method for in situ measurements of H2O in the UTLS.